Roles of thermospheric neutral wind and equatorial electrojet in pre-reversal enhancement, deduced from observations in Southeast Asia - P. Abadi; Y. Otsuka; HuiXin Liu; K. Hozumi; D. R. Martinigrum; P. Jamjareegulgarn; Le Truong Thanh; R. Otadoy (My University, 2021)
Previous studies have proposed that both the thermospheric neutral wind and the equatorial electrojet (EEJ) near sunset play important roles in the pre-reversal enhancement (PRE) mechanism. In this study, we have used observations made in the equatorial region of Southeast Asia during March–April and September–October in 2010–2013 to investigate influences of the eastward neutral wind and the EEJ on the PRE's strength. Our analysis employs data collected by the Gravity Field and Steady-State Ocean Circulation Explorer (GOCE) satellite to determine the zonal (east-west direction) neutral wind at an altitude of ~250 km (bottomside F region) at longitudes of 90°–130°E in the dusk sector. Three ionosondes, at Chumphon (dip lat.: 3.0°N) in Thailand, at Bac Lieu (dip lat.: 1.7°N) in Vietnam, and at Cebu (dip lat.: 3.0°N) in Philippines, provided the data we have used to derive the PRE strength. Data from two magnetometers — at Phuket (dip lat.: 0.1°S) in Thailand and at Kototabang (dip lat.: 10.3°S) in Indonesia — were used to estimate the EEJ strength. Our study is focused particularly on days with magnetically quiet conditions. We have found that the eastward neutral wind and the EEJ are both closely correlated with the PRE; their cross-correlation coefficients with it are, respectively, 0.42 and 0.47. Their relationship with each other is weaker: the cross-correlation coefficient between the eastward neutral wind and the EEJ is just 0.26. Our findings suggest that both the eastward neutral wind and the EEJ near sunset are involved in the PRE mechanism. Based on the weak relationship between these two parameters, however, they appear to be significantly independent of each other. Thus, the wind and the EEJ are likely to be influencing the PRE magnitude independently, their effects balancing each other.
Keywords: Equatorial electrojet; Electrojet; Magnetic dip; Sunset; Ionosphere and magnetosphere dynamics